Peran Pendidik dalam Membangun Pendidikan Transformasi Anak Usia Dini di KB Fathul Rahmah Dasan Poto Desa Rarang Tengah - Siti Malikah; Khairul Azmi; Mukhtar (MODELING: Jurnal Program Studi PGMI, 2025)
The purpose of this study was to determine the role of educators in building transformational early childhood education at KB Fathul Rahmah Dasan Poto, Rarang Tengah Village, in the 2024/2025 academic year. This research method used descriptive qualitative research, by attempting to describe the research results obtained in the field. The types of data used in this study are primary and secondary data with data sources consisting of the principal and educators. The data collection techniques used by the researcher were observation, interviews, and documentation. The data analysis techniques used were data reduction, data presentation, and drawing conclusions. The data analysis obtained was then processed in the form of words expressed in the form of descriptions or narratives. The results of this study indicate that the role of educators in building transformational early childhood education at KB Fathul Rahmah Dasan Poto, Rarang Tengah Village can be said to have been implemented quite well. In carrying out their roles, KB Fathul Rahmah Dasan Poto educators, Rarang Tengah Village, implemented a carefully designed learning planning strategy so that the learning process could run effectively and efficiently, participating in training conducted by the government for the independent curriculum and in the form of workshops.